2019
DOI: 10.1074/jbc.ra118.006178
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter forms stable dimers in the live cell plasma membrane in a phosphatidylinositol 4,5-bisphosphate–independent manner

Abstract: The human dopamine transporter (hDAT) regulates the level of the neurotransmitter dopamine (DA) in the synaptic cleft and recycles DA for storage in the presynaptic vesicular pool. Many neurotransmitter transporters exist as oligomers, but the physiological role of oligomerization remains unclear; for example, it has been speculated to be a prerequisite for amphetamine-induced release and protein trafficking. Previous studies point to an oligomeric quaternary structure of hDAT; however, the exact stoichiometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 75 publications
0
36
1
Order By: Relevance
“…These trimers apparently represent only a small fraction of the plasma membrane DAT in untreated cells based on western blotting detection and cross-linking with BS 3 , and are highly specific to DAT. By contrast, single-molecule microscopy analysis showed that about 35% of the plasma membrane DAT is constitutively dimeric (24). We did not observe SDS-resistant or BS 3 -linked dimer species of wt DAT detectable by western blotting, and our modeling predicts AIM-100/AL stabilization of DAT trimers by strong hydrophobic interactions, which may explain SDS-resistance of trimers ( Figure 7).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…These trimers apparently represent only a small fraction of the plasma membrane DAT in untreated cells based on western blotting detection and cross-linking with BS 3 , and are highly specific to DAT. By contrast, single-molecule microscopy analysis showed that about 35% of the plasma membrane DAT is constitutively dimeric (24). We did not observe SDS-resistant or BS 3 -linked dimer species of wt DAT detectable by western blotting, and our modeling predicts AIM-100/AL stabilization of DAT trimers by strong hydrophobic interactions, which may explain SDS-resistance of trimers ( Figure 7).…”
Section: Discussionmentioning
confidence: 56%
“…We did not observe SDS-resistant or BS 3 -linked dimer species of wt DAT detectable by western blotting, and our modeling predicts AIM-100/AL stabilization of DAT trimers by strong hydrophobic interactions, which may explain SDS-resistance of trimers ( Figure 7). Furthermore, DAT dimers were detected by single-molecule imaging due to their lateral mobility in the plasma membrane (24). By contrast, AIM-100 oligomers were mostly immobile (25), and therefore would not be detected by the method used in (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published work has shown that trimerization of hDAT is promoted by the binding of a heterocyclic drug (furopyrimidine AIM-100) 25 . DAT forms stable dimers in a PIP 2 - and CHOL-independent manner 22 , whereas for SERT, the formation of oligomers is promoted by the binding of PIP 2 (ref. 24 ).…”
Section: Modulation Of Function By Small Moleculesmentioning
confidence: 99%
“…Computational analyses identified that this interaction can stabilize additional intermediates in the ion-release pathway thereby facilitating altered Na + release pathways leading to dopamine transport (Razavi et al, 2018). Also, PIP2 interactions are suggested to mediate stable oligomer formation with hSERT (Anderluh et al, 2017) although hDAT oligomerization is observed to be PIP2 independent in single-molecule studies (Das et al, 2019). Most of the interactions with PIP2 were suggested to happen at the N-termini of the transporters, which are not part of the experimental structures as they have been removed due to their disordered characteristics.…”
Section: Role Of Lipids In Transport Functionmentioning
confidence: 99%